Relationship between Exhaled Nitric Oxide and Small Airway Lung Function in Normal and Asthmatic Children - Nakajima, Naoki; Mochizuki, Hiroyuki; Muramatsu, Reiko; Hagiwara, Satomi; Mizuno, Takahisa; Arakawa, Hirokazu (Allergology International, 2011)
In children, exhaled nitric oxide (eNO) is usually confounded by factors such as age and height. We evaluated the relationship between eNO and lung function by minimizing the effects of aging and height. In Study 1, the subjects comprised 738 elementary school children and junior high school children (aged 6 to 15 years, 366 males and 372 females). They were divided into two groups according to age (6–10 years and 11–15 years). A height range was determined by a histogram of height in each group. In Study 2, lung function, respiratory resistance and eNO level were measured in age- and height-limited groups. In Study 1, total of 148 younger children ranging in height from 120 to 130 cm and 180 older children ranging in height from 148 to 158 cm participated in Study 2. The level of eNO among asthmatic children was higher than that of normal children in both the younger and the older groups. The decrease in forced expiratory volume in 1 second (FEV1) and other parameters of central airway resistance did not correlate with the eNO level. However, the small airway parameters of MMEF and V25/HT in older asthmatic children, and V25/HT and R5-R20 in younger asthmatic children inversely correlated with eNO. Our data suggest that eNO level inversely correlates with small airway narrowing, and airway inflammation has a significant effect on small airway lung function in asthmatic school children.